Tetracycline as local drug delivery in treatment of chronic periodontitis: A systematic review and meta-analysis - Prasad Shyamrajan Nadig; Monali Amit Shah (Wolters Kluwer Medknow Publications, 2016)
Background: The aim of the present meta-analysis is to determine the efficacy of tetracycline group of antibiotics as local drug delivery agents in the treatment of chronic periodontitis. Materials and Methods: MEDLINE, EBSCO, Cochrane database, and Google Scholar were used to identify studies in English published up to January 31, 2017. An additional hand search of relevant journals and of the bibliographies of the paper identified was also performed. Articles retrieved were screened using specific inclusion criteria by two independent reviewers. Randomized control trials investigating the effect of tetracycline group of antibiotics as local drug delivery agents in chronic periodontitis were included in the study. Results: Ten relevant articles were selected for the meta-analysis, of which five articles were retrieved after electronic search, three articles were included after hand search, and two unpublished articles were included. The number of patients in studies ranged from 13 to 140 sites with mean age ranging from 20 to 75. A total of 588 sites were treated using tetracycline group of antibiotics as local drug delivery agents in the treatment of chronic periodontitis. The meta-analysis showed standard difference in mean −1.02 mm (95% confidence interval [CI] 0.28, 1.75) for clinical gain in attachment in favor of tetracycline group. Standard difference in mean for probing depth (PD) was 1.20 mm (95% CI 0.57, 1.87) in tetracycline group. Conclusion: The results of this meta-analysis showed a significant improvement in periodontal parameters such as CAL, PD, and sulcular bleeding index in favor of tetracycline as local drug delivery compared to placebo.